Chromosomal similarity between the Scaly-headed parrot (Pionus maximiliani), the Short-tailed parrot (Graydidascalus brachyurus) and the Yellow-faced parrot (Salvatoria xanthops) (Psittaciformes: Aves): a cytotaxonomic analysis - Caparroz, Renato; Duarte, José Maurício Barbanti [UNESP] (Sociedade Brasileira de Genética, 2004)
Behavior, morphology, allozyme studies and DNA hybridization and sequencing data all suggest the independent evolution of the Old and New World parrots and support tribe status for the American species, although the phylogenetic relationships within this tribe are still poorly understood. A previous study has shown that the Yellow-faced parrot (Amazona xanthops Spix 1824) exhibits large karyotypic differences compared to the other Amazona species and suggested that this species should be renamed Salvatoria xanthops, although the relationships between S. xanthops and the other New World parrots remain unclear. In the present work, we describe the karyotype of the Scaly-headed parrot (Pionus maximiliani, Kuhl 1820) and the karyotype and C-banding pattern of the Short-tailed parrot (Graydidascalus brachyurus, Kuhl 1820) and compare them to the karyotype and C-banding pattern of S. xanthops, as well as to the karyotypes of other New World parrots. The chromosomal similarity between these three species and the karyotypic differences between them and other New World parrots suggest that G. brachyurus and S. xanthops are sister species and are most closely related to members of the genus Pionus.
Keywords: chromosome; karyotype; cytotaxonomy; psittaciformes; parrots